On the Study of Semilinear Fractional Differential Equations Involving Atangana-Baleanu-Caputo Derivative - Khalid Hilal; Ahmed Kajounı; Samira Zerbib (Universal Journal of Mathematics and Applications, 2023)
This work aims to study the existing results of mild solutions for a semi-linear Atangana-Baleanu-Caputo fractional differential equation with order $ 0 < θ < 1 $ in an arbitrary Banach space. We rely on some arguments to present the mild solution to our problem in terms of an $ θ $-resolvent family. Then we study the existence of this mild solution by using Krasnoselskii's fixed point theorem. Finally, we give an example to prove our results.